Development of Aqidah Akhlak Model to Forming the Student Characters in Islamic Education - Razaq, Abd Rahim (International Journal of Psychosocial Rehabilitation, 2020)
--- Today, there has been behavior change in young generation. Dishonest behavior that shown by people who become role models for the young generation has become the easiest model to followed. To avoid the young generation from the negative behavior that easily to affects them, it need character education through morality as a way to develop and forming the behavior and character of the students, which aims to instill and enhance faith to them. This study is intended to find a model of moral education that can be applied in the classroom to encourage the moral formation of students based on Islamic values. The research method used qualitative approach, where in-depth interviews are conducted to students to get the right information about the types of moral education that have influenced them. Therefore the student could changes to be better and responsible behavior. From this study, it is known that proper communication between humans is the main factor that determines a person can receive teaching and influence from other parties of student behavior. The freedom of communication that is no longer restricted by strict manners, it makes the older generation, such as lecturers and parents, forced to follow the communication style of the young generation, that they can accepted and imitated by them. The consistency of the words and actions of a person is also a reason for students to imitate their moral character. Based on the results of this study, the model of moral development for the young generation is most appropriate to be applied in classroom teaching, which using the method of Qishshah (storytelling), the method of Uswah (exemplary), and the Ta'widiyah (habituation) method.